THE POWER OF PERSUASION: THE IMPACT OF PRODUCT REVIEWS, AFFILIATE MARKETING, AND LIVE CONTENT ON CONSUMER BEHAVIOR - Nadila, Desi; Kurlillah, Anis; Safarida, Nanda (Faculty of Islamic Economic and Business (FEBI), Sayyid Ali Rahmatullah State Islamic University (UIN SATU) Tulungagung, 2024)
This research investigated the persuasive power of product reviews, affiliate marketing, and live content on consumer behavior within the burgeoning TikTok Shop platform. As Indonesia experienced rapid technological and information advancements, TikTok Shop emerged as a prominent digital marketing tool, blurring the lines between entertainment and commerce. This quantitative field study specifically examined the impact of these persuasive elements on impulse buying behavior within the platform. Primary and secondary data were gathered through questionnaires and documentation, targeting 100 TikTok Shop users in Langsa City using a purposive sampling technique. Multiple linear regression analysis revealed a significant and positive combined effect of product reviews, affiliate marketing, and live content on impulse buying within TikTok Shop. The adjusted R-Squared value of 0.740 indicated that these persuasive elements collectively explained 74% of the variance in impulse buying behavior, highlighting their substantial influence on consumer decisions within the platform. While the remaining 26% was attributed to external factors not explored in this study, the research shed light on the persuasive power of TikTok Shop's marketing strategies. This study contributed to understanding how product reviews, affiliate marketing, and live content shaped consumer behavior and the potential implications for impulse buying within the increasingly popular TikTok Shop ecosystem.